Measurement of energy distribution for low power nanoflares - Bogachev S.A.; Erkhova N. F. (Solar-Terrestrial Physics, 2023)
We propose a method to measure the energy distribution of low-energy flares (nanoflares) in the energy range below 1023 erg. As an example, we measured the spectrum of nanoflares in the 1021–1026 erg range for two Sun’s frames observed by the SDO/AIA telescope in the 171 Å channel. Nanoflares are shown to have the power law spectrum in the 1022–1026 erg range. The spectral index is approximately constant, i.e. energy-independent. For energies below 1022 erg, the spectrum begins to collapse. For lower energies, below 1021 erg, the method does not give statistically significant results due to major errors. The results of the study indicate that solar nanoflares can be detected up to 1021–1022 erg energies. Results have previously been reported only for 1023 erg and above. The total energy flux of nanoflares in the energy range above 1022 erg, according to our data, is P2104 erg cm–2 s–1, which is about 15 times less than heating losses of the solar corona.